Strategi Pembelajaran dalam Memotivasi Siswa Guna Pemahaman Nilai-Nilai Sholat di MTs Ittihadul Ulum Kota Lubuklinggau - Triyamti Triyamti (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
The porpose of this research is: 1) How are the strategies and analysis of Fiqh teachers in motivating students to un- derstand and practice the values of prayer at MTs Ittihadul Ulum in Lubuklinggau City ?, 2) What are the obstacles and factors supporting Fiqh teachers in motivating students to understand and practice values pray at MTs Ittihadul Ulum, Lubuklinggau City ?. This type of research is field research (field research) with a qualitative approach. The results showed that the strategy of Fiqh teachers in motivating students to understand and practice the values of prayer at MTs Ittihadul Ulum in Lubuklinggau City was an individual approach to students. The factors for increasing the learning outcomes of Islamic Civilization History at MTs Ittihadul Ulum are 1) adding to the Fiqh textbook, 2) simple tools and materials in the form of cardboard or available materials, 3) To arouse students’ interest by giving praise and giving satisfactory grades to students. students, and 4) The solu- tion to solve the problems faced by Fiqh teachers is to give understanding to parents that textbooks have a major influence on the teaching and learning process.